1988
DOI: 10.1159/000266734
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Human Diseases as Oxidative Risk Factors in Cataractogenesis

Abstract: In this study we have investigated the oxidative metabolism of red blood cells (RBC), plasma, serum, aqueous humor, and lens of healthy subjects and of age-matched cataractous patients with and without diabetes. Reduced and oxidized glutathione (GSH, GSSG) levels in RBC were similar among the three groups. Plasma levels of GSSG were higher in diabetics than in cataractous and control subjects. No differences in plasma content of GSH were noted among the three groups. The activity of the enzyme glucose-6-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 25 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…Recently, we have demonstrated that CRF patients have very low levels of GSH in RBCs and increased amounts of oxidized glutathione (GSSG) in plasma [3,9]; moreover, in these patients the biological liquid oxidant activity of se rum, an expression of the free radicals concentration [10], is also elevated compared to the levels found in healthy volun teers [11]. For these reasons we have parenterally adminis tered GSH to CRF patients to verify its efficacy on anemia in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that CRF patients have very low levels of GSH in RBCs and increased amounts of oxidized glutathione (GSSG) in plasma [3,9]; moreover, in these patients the biological liquid oxidant activity of se rum, an expression of the free radicals concentration [10], is also elevated compared to the levels found in healthy volun teers [11]. For these reasons we have parenterally adminis tered GSH to CRF patients to verify its efficacy on anemia in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…level and cataract [8,11,[20][21][22], Some reported a positive relation between serum a-Toc. level and cataract prev alence [8,11,20], and others found no corre lation [21,22], Studies of a correlation be tween lenticular a-Toc. concentration and cataract formation are few [16,23], and their conclusions also differ.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that a major factor involved in the development of cataract is oxidative insult [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Oxidative stress associated with the formation of lipid peroxides is suggested to contribute to pathological processes in aging and systemic diseases, such as diabetes, atherosclerosis, chronic renal failure, inflammation, and retinal degenerative diseases known as statistically significant risk factors for cataract [21][22][23][24][25].…”
Section: O X I D a T I V E S T R E S S I N T E N S I T Y I N L E N S mentioning
confidence: 99%